Follicle‐stimulating hormone synthesis and fertility depend on SMAD4 and FOXL2. Issue 8 (16th April 2014) - Fortin, Jérôme; Boehm, Ulrich; Deng, Chu‐Xia; Treier, Mathias; Bernard, Daniel J.
Abstract : Follicle‐stimulating hormone (FSH) is an essential regulator of gonadal function and fertility. Loss‐of‐function mutations in the FSHB/Fshb gene cause hypogonadotropic hypogonadism in humans and mice. Both gonadotropin‐releasing hormone (GnRH) and activins, members of the transforming growth factor β (TGFβ) superfamily, stimulate FSH synthesis; yet, their relative roles and mechanisms of action in vivo are unknown. Here, using conditional gene‐targeting, we show that the canonical mediator of TGFβ superfamily signaling, SMAD4, is absolutely required for normal FSH synthesis in both male and female mice. Moreover, when the Smad4 gene is ablated in combination with its DNA binding cofactor Foxl2 in gonadotrope cells, mice make essentially no FSH and females are sterile. Indeed, the phenotype of these animals is remarkably similar to that of Fshb ‐knockout mice. Not only do these results establish SMAD4 and FOXL2 as essential master regulators of Fshb transcription in vivo, they also suggest that activins, or related ligands, could play more important roles in FSH synthesis than GnRH.—Fortin, J., Boehm, U., Deng, C.‐X., Treier, M., Bernard, D. J. Follicle‐stimulating hormone synthesis and fertility depend on SMAD4 and FOXL2. FASEB J. 28, 3396–3410 (2014). www.fasebj.org